Representasi Loyalitas dalam Dialog dan Interaksi Karakter Roronoa Zoro di Serial One Piece: Kajian Humaniora - Anhar, Anhar; Febriani, Shella Nur; Fitria, Rizka; Ramadhani , Selvi Tiara (Indo-MathEdu Intellectuals Journal, 2024)
In the One Piece series, Roronoa Zoro's loyalty to Monkey D. Luffy is not just a comradeship, but a strong bond of brotherhood. This research explores the importance of fostering individual trust and commitment in facing common challenges. Through the analysis of dialogue and interaction between Zoro and Luffy, this research reveals that the representation of loyalty serves as a social construct that is reflected in the actions and communication of characters. Using a critical discourse analysis and narrative study approach, the study examined five episodes in the Thriller Bark Arc and several other episodes, highlighting key moments that demonstrate Zoro's dedication. The technique used is qualitative descriptive, through four stages, namely data collection, data reduction, data presentation, and conclusion drawing. The results of the analysis show that Zoro's loyalty is influenced by the personal code of honor, the promise to Kuina, the respect for Luffy, as well as the shared experience that strengthens the emotional bond. This loyalty inspires readers about the true meaning of commitment and friendship in the context of popular culture, making it a vivid example of values that are widely accepted among a global audience